The Bourne Ultimatum - Book 3 - Ludlum, Robert, 1927-2001. (New York : Bantam Books, 2012)
A mild-mannered professor is forced to assume again the deadly alter ego he created in Vietnam years ago as part of the Medusa Brigade.
Keywords: Carlos, -- the Jackal -- Fiction; United States -- Central Intelligence Agency -- Fiction; Bourne, Jason (Fictitious character) -- Fiction; Terrorists -- Fiction; Action and adventure fiction; Spy fiction; Thrillers (Fiction)